2021
DOI: 10.1111/hsc.13363
|View full text |Cite
|
Sign up to set email alerts
|

Association between health literacy and leisure time physical activity among Lithuanian adolescents

Abstract: Recently, discussion of the potential of health literacy (HL) for health promotion has increased; however, clear evidence illuminating the relationship between adolescents' HL and their physical activity (PA) remains scarce. This study aimed to assess the association between adolescents' HL and leisure time PA. A representative cross-sectional study was conducted with 2,369 Lithuanian adolescents aged 13-16 years. A self-reported questionnaire gathered information regarding HL, leisure How to cite this article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Moreover, adolescents engaged in organized leisure time activities experience positive health benefits, regardless of family structure or socioeconomic status. However, adolescents living in non-nuclear families or low socioeconomic conditions are less likely to partake in organized leisure activities (Badura et al, 2021 ), which is also supported by Sukys et al ( 2021 ) showing that high socioeconomic status or having high levels of health literacy is associated with higher physical activity levels.…”
Section: Introductionmentioning
confidence: 79%
“…Moreover, adolescents engaged in organized leisure time activities experience positive health benefits, regardless of family structure or socioeconomic status. However, adolescents living in non-nuclear families or low socioeconomic conditions are less likely to partake in organized leisure activities (Badura et al, 2021 ), which is also supported by Sukys et al ( 2021 ) showing that high socioeconomic status or having high levels of health literacy is associated with higher physical activity levels.…”
Section: Introductionmentioning
confidence: 79%
“…Gomes et al [ 31 ] report that leisure time exercise may positively influence mental health both directly and indirectly by reducing the time spent by youth in sedentary activities. These types of activities are also bidirectionally associated with health literacy, which may not only improve adolescents’ health status, but also their knowledge and understanding of the indicators of health and, as a consequence, influence their lifestyle choices [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also showed that people with poor health literacy are not likely to practice healthy behaviors, including PA [ 46 ], and are therefore at an increased health risk for disease [ 47 ]. A study on adolescents showed that moderate or high health literacy is positively associated with PA in leisure time [ 48 ]. However, unlike the cases of adults and adolescents, outdoor play and PA among preschool children is highly influenced by their parents’ awareness and positive actions for healthy health behaviors [ 49 ].…”
Section: Discussionmentioning
confidence: 99%